EXERCISE AS AN IMPORTANT MEANS OF WELLNESS - Mamayusupov Otabek Valiyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
in our country there is a need to introduce into practice specific programs that contribute to the strengthening of the health of the population in the field of physical education and sports, to widely involve young people in sports and to qualify talented athletes from among them, to form national teams with skilled athletes who provide high results in sports and create additional The problems of development and practical testing of advanced pedagogical technologies have attracted the attention of many scientists as scientific objects. In this study, an attempt was made to cover these problems more widely, to promote consistent mastery of coaching skills for students. In the study, the means for a gymnastics lesson are given as an example. It is hoped that the set of classes given as a model will allow specialists to deepen their knowledge.